Pengaruh Kombinasi Pseudomonad Flouresen Dan Em4 Dalam Menghambat Pertumbuhan Blood Disease Bacteria (Bdb) Penyebab Penyakit Darah Tanaman Pisang Secara In Vitro - Maemunah Maemunah (UNIVERSITAS NEGERI PADANG, 2017)
Blood Disease Bacteria is one obstacle in cultivation of bananas. BDB can be controlled using biological agents. Biological agents that can be used to control of blood diseases are Pseudomonad fluorescent and microorganisms in EM4. Pseudomonad fluorescent used as biological agents because of its ability to produce antimicrobial compounds such as siderophores, antibiotics, volatile and cyanide. other than that, the EM4 microorganisms can produce antimicrobial against several bacterial pathogens. This study aims to determine the effect of combination Pseudomonad fluorescent and EM4 to inhibit the growth of BDB in vitro. This research was conducted in January 2016 in the Laboratory of Microbiology Department of Biology FMIPA UNP. Research using a completely randomized design (RAL) with 6 treatments and 3 replications. The study treatment is a combination of Pseudomonads fluorescent and EM4. The observation was done by measuring the clear zone formed around the paper disc. Data were analyzed using analysis of variance (ANOVA) and the test of Duncan New Multiple Range Test (DNMRT) at 5% level. The research proves that the combination resulted in inhibition zone around the paper disc. Inhibition zone shows that the combination inhibits the growth of BDB in vitro. Inhibition zone is formed as fluorescent Pseudomonads and microbes on EM4 produce secondary metabolites that can inhibit the growth of BDB.Key Word: Pseudomonad flourecent, BDB, EM4